Association between lifestyle and mental health of Kyiv children in the second year of the war (Environment & Health, 2024)
The aim of the study was to research changes in the daily routine and learning of schoolchildren during the war and their association with mental health.Materials and methods: A study of daily routines and mental health of schoolchildren in Kyiv was conducted using an online questionnaire. Informed consent was obtained from parents. For analyzing 1417 questionnaires were selected (743 boys, 674 girls). The study of responses to the questionnaires made it possible to determine the weekly duration of physical activity (PA) of light (LPA) and moderate and high-intensity physical activity (MVPA), the duration of sedentary activity (SB) and sleep, as well as to determine the gradation of anxiety-depressive indicators and signs of post-traumatic stress disorder (PTSD). The formats of the learning process were evaluated (full-time, distance, mixed). The data obtained were also compared with the data at the beginning of the full-scale invasion. Statistical methods of data obtained were used.Results: The study showed that during the war, Kyiv schoolchildren’s daily routine and level of physical activity changed. In the spring of 2023, (47.0±1.4)% of Kyiv schoolchildren had full-time learning, (19.3±1.1)% - in distance learning, (32.9±1.3_% - in mixed learning, in contrast to 2022, when children learned mainly in a distance format. In 2023, there was a 6.4% decrease in sleep duration compared to 2022. Additionally, there was a 19.2% increase in total physical activity due to LPA, while conversely, there was a 17.7% decrease in MVPA. In 2022, 23.1% of school-age children had the optimal level of MVPA (60 min/day), while in 2023, this percentage decreased to 11.3% (p
Keywords: school-age children; mental health; war; lifestyle; physical activity; anxiety and depression indicators; signs of post-traumatic stress disorder; learning format